Separating Electrons and Donors in BaSnO3 via Band Engineering - Prakash, Abhinav; Quackenbush, Nicholas F; Yun, Hwanhui; Held, Jacob; Wang, Tianqi; Truttmann, Tristan; Ablett, James M; Weiland, Conan; Lee, Tien-Lin; Woicik, Joseph C; Mkhoyan, K. Andre; Jalan, Bharat (Nano letters, 2019)
Separating electrons from their source atoms in La-doped BaSnO3, the first perovskite oxide semiconductor to be discovered with high room-temperature electron mobility, remains a subject of great interest for achieving high-mobility electron gas in two dimensions. So far, the vast majority of work in perovskite oxides has focused on heterostructures involving SrTiO3 as an active layer. Here we report the demonstration of modulation doping in BaSnO3 as the high room-temperature mobility host without the use of SrTiO3. Significantly, we show the use of angle-resolved hard X-ray photoelectron spectroscopy (HAXPES) as a nondestructive approach to not only determine the location of electrons at the buried interface but also to quantify the width of electron distribution in BaSnO3. The transport results are in good agreement with the results of self-consistent solution to one-dimensional Poisson and Schrödinger equations. Finally, we discuss viable routes to engineer two-dimensional electron gas density through band-offset engineering.